Numerical and experimental study of the electrofusion welding process of polyethylene pipes. Issue 1 (19th February 2014) - Chebbo, Ziad; Vincent, Michel; Boujlal, Adil; Gueugnaut, Dominique; Tillier, Yannick
<x xml:space="preserve">Abstract</x> The electrofusion welding process is widely used to join polyethylene components in gas distribution networks. This article provides experimental and 3D‐finite element tools capable of reproducing the major phenomena that occur during an electrofusion process. A specific version of the 3D‐ finite element model simulation software Forge® has been developed to take into account the fitting parameters such as polyethylene thermal properties (i.e., melting and crystallization kinetics, phase transition, and thermal contact resistance) and the electrical and geometrical settings (i.e., welding input parameters). From a numerical point of view, a well refined highly anisotropic mesh adaptation is applied to well capture the contact condition between the heat source and the polyethylene. The computed results (temperature, melted, and cold areas) were compared with experimental data and gave very good agreement in terms of temperature and liquid phase fraction distribution. POLYM. ENG. SCI., 55:123–131, 2015. © 2014 Society of Plastics Engineers